1876 Ala. Code 914 - (:unkn) unknown (My University, 1876)
§ 4315: Prohibited assault and battery of another with a cowhide, stick, or whip while in possession of a pistol or other deadly weapon with the intent to intimidate another to prevent the person from defending himself. Violators imprisoned not less than two nor more than twenty years.
Keywords: CARRY - INTENT TO COMMIT CRIME